1999
DOI: 10.1128/aac.43.4.947
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in GyrA and ParC Associated with Fluoroquinolone Resistance in Enterococcus faecium

Abstract: High-level quinolone resistance in Enterococcus faeciumwas associated with mutations in both gyrA andparC genes in 10 of 11 resistant strains. One low-level resistant strain without such mutations may instead possess an efflux mechanism or alterations in the other subunits of the gyrase or topoisomerase IV genes. These findings are similar to those for other gram-positive bacteria, such as Enterococcus faecalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 30 publications
5
28
1
2
Order By: Relevance
“…Two mutation events in each gene were found (Table 1), and both aa combinations (GyrA Arg83, ParC Ile80 or GyrA Ile83, ParC Arg80) have been described previously in E. faecium isolates with ciprofloxacin MICs ≥16 mg/L [25], [40], [41]. Moreover, the tetracycline resistance determinant tetM and the macrolide resistance determinant ermB were also found in three and four WGS isolates, respectively (Table S2).…”
Section: Resultssupporting
confidence: 52%
“…Two mutation events in each gene were found (Table 1), and both aa combinations (GyrA Arg83, ParC Ile80 or GyrA Ile83, ParC Arg80) have been described previously in E. faecium isolates with ciprofloxacin MICs ≥16 mg/L [25], [40], [41]. Moreover, the tetracycline resistance determinant tetM and the macrolide resistance determinant ermB were also found in three and four WGS isolates, respectively (Table S2).…”
Section: Resultssupporting
confidence: 52%
“…This indicates alternative resistance mechanisms or upregulation and downregulation of genes other than those investigated here but involved in higher expression of fluoroquinolone non-susceptibility, such as efflux pumps or topoisomerase protection genes [36,[43][44][45]. Several authors have also reported double mutations in parC and gyrA prevalent among high-level ciprofloxacin-resistant clinical isolates of E. faecium [19,20,34], whereas other reports demonstrated single parC mutations as sufficient to confer elevated ciprofloxacin MICs in natural isolates [17,33]. In some of the previous studies, sequential mutations were introduced by challenging test strains with growing concentrations of fluoroquinolones in vitro [36,37].…”
Section: Discussionmentioning
confidence: 81%
“…However, the respective strain collections were mostly limited or restricted in terms of time, geographical coverage or any homogeneity, thus not allowing any specific epidemiological conclusions [20,33,34]. Here, based on a comprehensive collection of clinical E. faecium isolated from German hospital patients between 1997 and 2007, we showed a permanent increase in their MICs for ciprofloxacin (Table 1).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our data revealed a high transfer rate (10 −4 –10 −5 ) for both, tetracycline and doxycycline resistance traits, indicating potential involvement of Tn 916 . Ampicillin and enrofloxacin resistance traits could not be transferred in vitro , possibly because the conferring resistance genes such as pbp5 or gyrA are commonly encoded on non-transferable regions of the chromosome [72], [73].…”
Section: Discussionmentioning
confidence: 99%